Effective Disposal of Biological and Pharmaceutical Waste: A Note to the Health Care Professional: Pharmaceutical Science-Industrial Pharmacy - Arigela Sai Likhitha; Hindustan Abdul Ahad; Chinthaginjala Haranath; Swamygari Satya Harsha; Kumbarthi Thanmayadivya; Gopavaram Sumanth; Ambati Nagarajeswari (International Journal of Life Science and Pharma Research, 2022)
The current appraisal aims to educate and give valuable information about disposal methods adopted in hospitals and health sectors. Many healthcare departments like microbiology labs, pharma industries, medical agencies, healthcare sectors all produce waste which usually contains unsafe materials that should not be exposed untreated to the atmosphere. In these health sectors, many types of wastes are separated as lab debris, chemical, and biological waste. These waste are rich in contaminants and pathogenic microbes which will be more lethal if they are not properly disposed of. The authors describe the various wastes and the definite discarding process to minimize costs and impact on the surroundings. Presently many of these sector professionals have some difficulty in disposal, these issues can be overcome by the systematic and easy plan described by the authors. Specific treatment must be required for this waste before they disposed off. This waste must be washed before introducing them into a particular disposable discard. Medical waste can be disposed of thoroughly as they contain infectious or non-infectious microorganisms. Biological and pharmaceutical waste must be disposed of, to prevent environmental hazards. Among the various approaches adopted for the disposing of these waste includes incineration, autoclaving, chemical disinfection, ignitability, etc. are popularly adopted. Each particular waste can be disposed of in a specific manner. The authors succeed in bringing the systematic approach in the disposal of waste in health care units and concludes that proper disposal is important to reduce the contamination and pollution of the environment and maintain a healthy atmosphere.